2004
DOI: 10.1159/000079487
|View full text |Cite
|
Sign up to set email alerts
|

Serial Topoisomerase II Expression in Primary Breast Cancer and Response to Neoadjuvant Anthracycline-Based Chemotherapy

Abstract: Objective: We analyzed the value of topoisomerase IIα (Topo II) in predicting the clinical response to anthracycline-based neoadjuvant chemotherapy in breast cancers and the potential changes in Topo II after chemotherapy. In parallel, HER2, which is commonly coexpressed with Topo II, and p53, a modulator of chemotherapy activity, were also analyzed. Methods: Forty-one patients with primary breast cancer and treated with neoadjuvant anthracycline-based chemotherapy (FAC or FEC) were included for the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 11 publications
2
18
0
1
Order By: Relevance
“…For instance, in a study by MacGrogan et al (25), the response to neoadjuvant chemotherapy was found to correlate with the immunohistochemical expression of TopoII, but not with that of HER-2. Similar results were reported by Martin-Richard et al (29). In another study (26), a favorable response to chemotherapy regimens containing anthracyclines and taxanes was more frequently observed in patients with tumors displaying either TopoII overexpression or gene amplification, and in those displaying HER-2 amplification.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For instance, in a study by MacGrogan et al (25), the response to neoadjuvant chemotherapy was found to correlate with the immunohistochemical expression of TopoII, but not with that of HER-2. Similar results were reported by Martin-Richard et al (29). In another study (26), a favorable response to chemotherapy regimens containing anthracyclines and taxanes was more frequently observed in patients with tumors displaying either TopoII overexpression or gene amplification, and in those displaying HER-2 amplification.…”
Section: Discussionsupporting
confidence: 87%
“…In two of these studies (29,30), changes in TopoII expression were found to correlate with response to treatment, but a consistent picture correlating these changes to prognosis has not yet emerged. Here, we show for the first time, that changes in the expression of TopoII are of prognostic value in patients with operable breast cancer receiving anthracycline-based chemotherapy prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A seminal study (140) analyzed the value of Topo2α in predicting clinical response to anthracycline-based neoadjuvant chemotherapy in breast cancers and its potential changes after chemotherapy. The study also looked at p53 and Her2 the latter being commonly coexpressed with Topo2.…”
Section: F Serial Changes In Expression Of Various Candidate Proteinmentioning
confidence: 99%
“…In another older French study among 79 patients treated with either low-dose FEC (epirubicin 50 mg/m 2 ) or with FEC100 (epirubicin 100 mg/m 2 ), there was no difference in the response rate with either regimen in HER2-negative tumours, but a much higher response in HER2-positive patients treated with FEC100 compared with the lower-dose regimen, suggesting a dose--response relationship for epirubicin in HER2-positive disease (Petit et al 2001). However, recently Martin-Richard et al (2004) have shown no correlation between HER2 status by IHC and response to anthracycline-based chemotherapy (FAC/FEC) in 41 patients receiving neoadjuvant therapy. Furthermore, Bonnefoi et al (2003) have also shown no correlation between HER2 status and treatment outcome for 187 patients receiving epirubicin-based neoadjuvant chemotherapy for locally advanced breast cancers.…”
Section: Neoadjuvant Anthracycline-based Chemotherapymentioning
confidence: 99%
“…The results were contradictory, with several studies supporting its role as a prognostic marker (Barnes et al 1993, Silvestrini et al 1993, MacGrogan et al 1995, Silvestrini et al 1996, Thor et al 1998, Chappuis et al 1999) and many failing to show this relationship (Elledge et al 1995, Sjogren et al 1996, Clahsen et al 1998, Broet et al 1999, Penault-Llorca et al 2003, Martin-Richard et al 2004. However, as is well known, the differing methodologies and antibodies used in these studies, and the failure to detect unstable p53 mutants, suggests that assessment of p53 status should be based on gene-sequencing methods for a proper evaluation of its role.…”
Section: P53 As a Marker For Chemotherapy Responsementioning
confidence: 99%